INTERACTION BETWEEN CULTURED ENDOTHELIAL CELLS AND ABNORMAL ANTITHROMBIN III "TOYAMA" - Sakuragawa, N; Saitoh, S; Takahashi, K (Thrombosis and Haemostasis, 1987)
Purpose: Abnormal antithrombin III(AT-III)Toyama showed non-affinity to heparin and heparinoid to show loss of immediate antithrombin activity. On the endothelial cells, there are heparinoids including heparan sulfate. We investigated on the interaction between cultured endothelial cells and abnormal AT-III"Toyama" from the viewpoint of antithrombin activity.Materials and methods: (1) Endothelial cell culture:^125I-labelled normal and abnormal AT-III were placed on the washed endothelial cultured cells in 0.2 ml of RPMI-1640 medium for 15 min at 37°C. The medium was suctioned off and the cell layer was washed with Hank's balanced salt solution. The cells were incubated with 1 ml of heparin(3 ug/ml) for 15 min at 4°C. The radioactivity in the supernatant was counted, and represented AT-III which bound to the cells surface. (2) Antithrombin activity: 0.23 ml of thrombin solution^ U/ml) and 0.03 ml of normal or abnormal AT-III plasma were mixed, and incubated on the cultured cell surface for 5 min at room temperature. The residual thrombin activity was assayed by 0.3 ml of the substrate (S-2238) solution(0.8mM)for 5 min. After these procedures,2 ml of 2% citric acid solution was added to stop the reaction, and 0D(405 nm) was recorded.Results: Abnormal AT-III showed reduced binding-activity to cultured cells to one fifth compared with normal AT-III, and the residual thrombin activity in the abnormal was higher compared with that in normal plasma.Conclusion: Abnormal AT-III showed less binding activity to the cultured endothelial cells, and less thrombin neutralizing activity to show thrombogenic tendency.